(3GdNHQ GdeYQH Yf GdCeQ GdeZQH GdMGd HGdCfOdS hKZhQ GdeZQHs - (3CHh GdaVd eMeO CHh QGS GdfGUQ GdMSfs; (3eMeO (B((3CHhQGS(B) (3CMeO Hf GdfGUQ, GdfGUQj GdLQHj,J (B1239 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdaGYd ai Ndbg eG jQjO CeG HYO ajbhd GdfGUQ Ydi YLGFH GdCNHGQ HeG LQi ai GdCfOdS s
(3BNQgG (B:s
(3JfJgi Hbhdg (B: (3hHjdGLHd cHjQ HERGA bGdi bdG heYfi de jJSf (B" (3de jbJOi HeG bHdg ef s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B18 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B25s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs